1994
DOI: 10.1097/00000658-199405000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Bioartificial Liver to Treat Severe Acute Liver Failure

Abstract: ObjectiveTo test the safety and efficacy of a bioartificial liver support system in patients with severe acute liver failure. Summary Background DataThe authors developed a bioartificial liver using porcine hepatocytes. The system was tested in vitro and shown to have differentiated liver functions (cytochrome P450 activity, synthesis of liverspecific proteins, bilirubin synthesis, and conjugation). When tested in vivo in experimental animals with liver failure, it gave substantial metabolic and hemodynamic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
6

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(77 citation statements)
references
References 23 publications
1
70
0
6
Order By: Relevance
“…[24][25][26] Primary hepatocytes is ideal source for bioartificial liver device but not practically suitable due such limitations like the availability of these cells is limited, and expansion of human hepatocytes in culture is difficult, even advanced culture condition, still finite number of cell division and then stop. Although the cryopreservation techniques has been suggested as a standard protocol for long term storage liver cell retaining their function.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Primary hepatocytes is ideal source for bioartificial liver device but not practically suitable due such limitations like the availability of these cells is limited, and expansion of human hepatocytes in culture is difficult, even advanced culture condition, still finite number of cell division and then stop. Although the cryopreservation techniques has been suggested as a standard protocol for long term storage liver cell retaining their function.…”
Section: Discussionmentioning
confidence: 99%
“…65,75,79,[87][88][89] Single cell suspensions, used in some devices because of their desirable transport properties, quickly lose metabolic capacity. 90 Some packed bed designs 77,78 and one hollow fiber device 91 seed cells on microcarriers before device assembly. While microcarriers provide Potential stem cell sources…”
Section: Bioreactor Designmentioning
confidence: 99%
“…Recent meta-analysis of data from 12 trials, involving 483 patients, confirmed that while the devices were not yet showing efficacy in treatment of acute liver failure, some degree of improved survival was seen in acute-onchronic liver failure [66]. The hepatocyte sources so far include porcine hepatocytes (sometimes cryopreserved) [67][68][69] and a human C3A hepatoma-derived cell line [70,71]. Developers of these devices have been able to address safety concerns of immune reaction, xenozoonosis and tumourigenicity sufficiently to move to Phase II/III clinical trials [65].…”
Section: Cell-based Therapiesmentioning
confidence: 99%